ChemInform Abstract: Data‐Driven Review of Thermoelectric Materials: Performance and Resource Considerations. Issue 41 (19th September 2013) - Gaultois, Michael W.; Sparks, Taylor D.; Borg, Christopher K. H.; Seshadri, Ram; Bonificio, William D.; Clarke, David R.
Abstract Review: a database of thermoelectric materials with more than 18000 data points is created on the basis of information from about 100 publications; 132 refs.